5x - 4(6-x)(x + 3) = (4-2x)(3-2x) + 2
(x - 1)3 - (3x + 2)(-12) = (x2 + 1)(x - 2) - x2
(3x -1)2 - (x +3)(2x-1) = 7(x + 1)(x -2) -3x
giải phương trình :
a,x^4+2x^3+5x^2+4x-12=0
b,(x+1)^3+(x-2)^3=(2x-1)^3
c,(x+1)^4+(x+3)^3=82
a) (x + 3)(x - 5) + (x + 3)(3x - 4) = 0
b) 2x(2x - 3) = (3 - 2x)(2 - 5x)
c) 2x3 + 6x2 = x2 + 3x
d) x2 - 5x + 6 = 0
e) (2x + 5)2 = (x + 2)2
a) \(9x^2-1=\left(3x-1\right)\left(5x+8\right)\)
b) \(2x^3-5x^2+3x=0\)
c) \(9x^2-16-x\left(3x+4\right)=0\)
d) \(\dfrac{5x+4}{3}-1=\dfrac{3x-2}{4}\)
Giải pt
(4x-3)^2-(2x+1)^2=0
3x-12-5x×(x-4)=0
(8x+2)×(x^2+5)×(x^2-4)=0
Giải các pt sau :
1/ ( 3x – 2 )( 4x +5 ) = 0
2/ 5(2x – 3) – 4( 5x -7 ) = 19 - 2( x +11)
3/ ( x2 – 2x + 1 ) – 4 = 0
4/ ( x - 1) 2 + ( x+ 3) 2 = 2 ( x -2 ) (x +1 ) + 38
5/ \(\frac{4x+3}{2}-2+3x=\frac{2x-1}{10}+\frac{19x+2}{5}-1\)
6/ \(\frac{2x+4}{5}+\frac{2x-12,4}{6}-\frac{x+3}{10}=4\)
Giúp mình với mọi người ơi !!!
giải phương trình:
a)(x-5)^2+3(x-5)=0
b)2x-1/3-5x+2/7=x+13
c)x-1/x+2-x/x-2=7x-6/4-x^2
a, 12 - 3. ( x - 2 ) = ( x + 2 ).( 1 - 3x ) + 2x
b, ( x + 5 ).( x + 2 ) = 3.( 4x - 2 ) + ( x - 5 )
c, \(\frac{x-5}{x^2-5x}-\frac{x-5}{2x^2-10x}=\frac{x+25}{2x^2-50}\)
d, 4x2 - 1 = ( 2x + 1 ).( 3x - 5 )
e, x2 - 5x + 6 = 0
Giải các phương trình sau bằng cách đưa về phương trình tích :
a) \(\left(2x+1\right)\left(3x-2\right)=\left(5x-8\right)\left(2x+1\right)\)
b) \(4x^2-1=\left(2x+1\right)\left(3x-5\right)\)
c) \(\left(x+1\right)^2=4\left(x^2-2x+1\right)\)
d) \(2x^3+5x^2-3x=0\)